A low-power memristor based on 2H–MoTe2 nanosheets with synaptic plasticity and arithmetic functions - Yu, T.; Zhao, Z.; Jiang, H.; Weng, Z.; Fang, Y.; Liu, C.; Lei, W.; Shafe, S.B.; Mohtar, M.N. (Elsevier, 2022)
Bionic artificial synapses based on 2D transition metal dichalcogenides are comparable to biological synapses due to the unique properties, which are important for building brain-like computing to break the energy and data throughput limit of the von Neumann architecture. In this work, a two-terminal memristor with vertical structure was fabricated by using 2H–MoTe2 nanosheet dispersion. The fabricated memristor based on the Cu/MoTe2/Si structure not only exhibits the stable bipolar nonvolatile resistive switching behavior but also implements the centralized distribution of threshold voltage, and the SET/RESET power can be as low as 0.86 μW/93 nW. Impressively, classical synaptic functions including long-term potentiation/long-term depression, excitatory postsynaptic currents, spike-timing-dependent plasticity, and paired-pulse facilitation were mimicked, which attribute to the formation and rupturing of Cu conductive filaments. Interestingly, the simple arithmetic functions can be operated. Therefore, this work provides a new solution for the development of synaptic devices and neural computing research in the future.